2017
DOI: 10.1002/zoo.21372
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying long‐term impact of zoo and aquarium visits on biodiversity‐related learning outcomes

Abstract: Zoos and aquariums aim to achieve lasting impact on their public audiences' awareness of biodiversity, its value, and the steps they can take to conserve it. Here, we evaluate the long-term educational impact of visits to zoos and aquariums on biodiversity understanding and knowledge of actions to help protect biodiversity. A minimum of two years after completing a repeated-measures survey before and after visiting a zoo or aquarium, the same participants were invited to take part in a follow-up online survey.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 12 publications
(22 reference statements)
0
33
0
Order By: Relevance
“…When analyzing conservation knowledge retention, some studies have found that visitors’ conservation knowledge and interest persisted after a zoo visit (Jensen, 2014; Moss et al, 2015), but this new understanding rarely results in new conservation actions (Adelman et al, 2010; Miller et al, 2013). However, other studies suggest zoos prompt visitors to rethink their roles in conservation issues after their visit (Falk et al, 2007; Clayton et al, 2017; Jensen et al, 2017). While this is an emerging area of research interest, several studies support that the level and type of engagement with conservation and animals during the zoo experience affect not only visitors’ knowledge retention but also post-visit behavior.…”
Section: Discussionmentioning
confidence: 99%
“…When analyzing conservation knowledge retention, some studies have found that visitors’ conservation knowledge and interest persisted after a zoo visit (Jensen, 2014; Moss et al, 2015), but this new understanding rarely results in new conservation actions (Adelman et al, 2010; Miller et al, 2013). However, other studies suggest zoos prompt visitors to rethink their roles in conservation issues after their visit (Falk et al, 2007; Clayton et al, 2017; Jensen et al, 2017). While this is an emerging area of research interest, several studies support that the level and type of engagement with conservation and animals during the zoo experience affect not only visitors’ knowledge retention but also post-visit behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Many interpretive displays and programs in these settings aim to connect visitors with new information or resources, promote environmental literacy, or influence behaviors to augment environmental stewardship (Benton, 2009). Educational exhibits and programs at these facilities can stimulate conservation interest, awareness, enthusiasm, and advocacy (Briseño-Garzón et al, 2007;Falk & Adelman, 2003;Jensen et al, 2017;Wyles et al, 2013). Over 200 million people visit World Association of Zoos and Aquariums facilities around the globe annually, with U.S. facilities hosting 183 million people each year (Association of Zoos & Aquariums, 2020).…”
Section: Learning About Environmental Issues At Aquaria Zoos Museums and Parksmentioning
confidence: 99%
“…Exhibits and educational campaigns with effective messaging, and those which link conservation goals to concrete everyday life, can empower people and ultimately turn behavioral intentions into actions (e.g., Ballantyne et al, 2007;Chase et al, 2009;Korkala et al, 2014;Leisher et al, 2012;Napper & Thompson, 2020;Sujata et al, 2019). Zoos and aquaria can increase knowledge of conservation-related concepts in both the immediate and long-term (Jensen et al, 2017). In fact, positive effects from visits to parks, zoos, and aquaria can persist for years post-visit (Ballantyne et al, 2018).…”
Section: Learning About Environmental Issues At Aquaria Zoos Museums and Parksmentioning
confidence: 99%
“…Modern zoological institutions manage their collections in pursuit of several objectives which require resources and face constraints: education, outreach and engagement, sustainable management of the ex situ population, and support for in situ research and conservation (e.g., Gilbert & Soorae, ; Jensen, Moss, & Gusset, ). Unfortunately, six of the eight extant bear species are of conservation concern (IUCN Operations Intelligence Center, ; http://www.iucn.org), thus zoo‐housed bears—charismatic and popular among zoo visitors—may be effective conservation ambassadors for their wild counterparts.…”
Section: Introductionmentioning
confidence: 99%